Piezoelectrically mediated acoustic phonon tunneling - Geng, Zhuoran (2023)
Although purely acoustic waves cannot exist in vacuum by definition, an acoustic phonon can infact "jump" or "tunnel" across a vacuum gap between two piezoelectric solids. The dissertation presents the author’s work to provide a generally applicable theoretical formulation and an experimental demonstration of acoustic phonon tunneling between arbitrarily an isotropic and oriented piezoelectric crystals. Within the continuum an isotropic linear elasticity theory and the quasistatic approximation, this work solves the acoustic wave tunneling problem with two different approaches for a plane-plane geometry, acquiring the solutions of reflection and transmission of all the partial waves for any incoming wave mode, taking fully into account mode conversions. Such formalism can be applied to a practical numerical or even ananalytical implementation, as a few chosen analytical and numerical examples demonstrate. A strikingly simple resonant tunneling condition was discovered in this work, which leads to the complete tunneling of an acoustic phonon, a unity transmission of the acoustic wave across vacuum without reflection. The detailed analytical proof and numerical demonstration of such complete phonon tunneling are presented. Furthermore, this formalism was applied to investigate the heat flux associated with the phonon tunneling mediated by piezoelectricity. A few numerical results are demonstrated and compared with other near-field heat transfer mechanisms. In particular, this work shows that such heat transfer is significant when a vacuum gap size is smaller than the phonon characteristic wavelength, and even becomes the dominant mechanism at temperatures lower than 50K. Lastly, an experimental demonstration of the heat transfer mediated by acoustic phonon tunneling is presented, using two suspended piezoelectric microscopic beams at sub-kelvin temperatures. The results of the measurements provide qualitative evidence of the heat transfer, with comparisons between different vacuum gap widths and with non-piezoelectric devices. However, the quantitatively determined transferred power is not in good agreement with the theoretical estimations, and possible causes of the discrepancy are discussed.